Espécies de Bacillus no controle de Meloidogyne incógnita e Meloidogyne javanica in vitro e na cana-de-açúcar - Ferreira, Rivanildo Junior [UNESP] (2015)
The sugar-cane crop is very important to Brazilian economy. Phytonematodes are among the main limitating factors of such culture causing great losses. Chemical nematicides are harmful to humans, environment, harvested products, and are the main method used to manage the populations of these nematodes. Biological control have been a sustainable alternative to manage these nematodes. The aim of the present study was to evaluate Bacillus species for control Meloidogyne incognita and M. javanica in vitro and in sugar cane plants. We set assays in laboratory conditions in a completely random design with the treatments: Cadusafós 200 CS (14 L/ha), B. subitilis, B. firmus, B. amyloliquefaciens (1 and 10 L/ha) and a control (water). The pot assay, in a semi-field condition, had a completely random design with the treatments: B. subtilis (10 L/ha), B. firmus (10 L/ha), B. amyloliquefaciens (10 L/ha), Carbofurano 350 SC, with five replicates and two evaluation periods (100 and 150 days after inculation and application of treatments). At laboratory assay B. firmus (10 L/ha) was the most efficient in decreasing the M. javanica J2 eclosion and were statistically similar to the chemical nematicide tested. For M. javanica J2 mobility, B. subtilis (10 L/ha) and B. amyloliquefaciens (1 and 10 L/ha) cause nematode mortality, but lower than that presented by the chemical. To M. incognita, B. firmus (10 L/ha) provides higher J2 eclosion. For the M. incognita J2 mobility, Cadusafos 200CS (14 L/ha) caused higher mortality. In the pot assay, all treatments increase the number of tillers but do not control the nematodes